2019
DOI: 10.1016/j.amepre.2018.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Food Environment and Dementia Incidence: the Japan Gerontological Evaluation Study Cohort Survey

Abstract: Introduction Interventions targeting built environmental factors may encourage older people to engage in favorable behaviors and decrease dementia risk, but epidemiologic evidence is limited. This study investigated the association between neighborhood food environment and dementia incidence. Methods A 3-year follow-up (2010–2013) was conducted among participants in the Japan Gerontological Evaluation Study, a population-based cohort study of older adults aged ≥65 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 34 publications
0
55
0
Order By: Relevance
“…This study used 400 m and 800 m buffers as a proximate activity space for older people in their daily life. Although most existing studies also generated buffers based on participants’ residences [ 11 , 12 ], whether older people visited these green and blue spaces or travelled outside of local areas is not known. Although physical distances to the nearest amenities were measured in this study, other features of built environment such as availability of public transport, pavement conditions and street network might also affect the accessibility to amenities including those that might be at a distance [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study used 400 m and 800 m buffers as a proximate activity space for older people in their daily life. Although most existing studies also generated buffers based on participants’ residences [ 11 , 12 ], whether older people visited these green and blue spaces or travelled outside of local areas is not known. Although physical distances to the nearest amenities were measured in this study, other features of built environment such as availability of public transport, pavement conditions and street network might also affect the accessibility to amenities including those that might be at a distance [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study echo the complexity of relationships reported from earlier studies. Research from US, Japan and Hong Kong has included different measures related to local amenities, with inconclusive results for cognitive health in later life [11][12][13]. Here, living in an area with poor access to daily life amenities (post offices or convenience stores) was found to be associated with higher odds of dementia in both cohorts.…”
Section: Interpretation Of Findingsmentioning
confidence: 90%
See 2 more Smart Citations
“…Previous studies have shown that the food environment might impact incidence of mortality and dementia in older people [10,11]. If one’s main reason for going out is to shop at a neighborhood grocery store, food store availability might influence the incidence of functional disability in many older adults.…”
Section: Introductionmentioning
confidence: 99%